Association of plain water intake with risk of all-cause and cause-specific mortality in individuals with non-alcoholic fatty liver disease or metabolic dysfunction-associated steatotic liver disease - Zhao, Na; He, Yun; Li, Yuan; Zhang, Ning; Wang, Yan (Frontiers in Nutrition, 2024)
Non-alcoholic fatty liver disease (NAFLD) or Metabolic dysfunction-associated steatotic liver disease (MASLD)-related mortality have increased dramatically in past decades. Our study aims to investigate the association between plain water and this prevalent metabolic disease, as water plays a crucial role in regulating metabolic processes. A total of 3,543/3,428 individuals with NAFLD/MASLD were included in this study from National Health and Nutrition Examination Survey (NHANES). Daily plain water intake was recorded, and mortality status was tracked until December 31, 2019. Multivariate Cox regression models and restricted cubic spline (RCS) regression models were used to assess the association between plain water intake and long-term all-cause as well as cause-specific mortality among participants with NAFLD/MASLD. Furthermore, we investigated the relationship between substituting other beverages with plain water intake and the risk of mortality. The multivariate Cox regression analyses revealed a significant association between higher plain water intake and lower all-cause mortality, cerebrovascular diseases mortality, and cancer mortality in both NAFLD or MASLD patients. Dose-response analyses revealed a non-linear trend between plain water intake and mortality among NAFLD/MASLD patients. Additionally, replacing sugar or artificial beverages with plain water was linked to reduced all-cause mortality, cerebrovascular diseases mortality, and cancer mortality in patients with NAFLD/MASLD. Higher plain water intake is independently linked to lower risk of all-cause, cerebrovascular diseases mortality, and cancer mortality in NAFLD/MASLD patients. Increasing plain water intake may be an effective way for these patients to reduce their risk of mortality.